Mathematical Modeling and Applications in Nonlinear Dynamics - Luo, Albert C.J.; Merdan, Hüseyin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book covers nonlinear physical problems and mathematical modeling, including molecular biology, genetics, neurosciences, artificial intelligence with classical problems in mechanics and astronomy and physics. The chapters present nonlinear mathematical modeling in life science and physics through nonlinear differential equations, nonlinear discrete equations and hybrid equations. Such modeling can be effectively applied to the wide spectrum of nonlinear physical problems, including the KAM (Kolmogorov-Arnold-Moser (KAM)) theory, singular differential equations, impulsive dichotomous linear systems, analytical bifurcation trees of periodic motions, and almost or pseudo- almost periodic solutions in nonlinear dynamical systems. Provides methods for mathematical models with switching, thresholds, and impulses, each of particular importance for discontinuousprocesses Includes qualitative analysis of behaviors on Tumor-Immune Systems and methods of analysis for DNA, neural networks and epidemiology Introduces new concepts, methods, and applications in nonlinear dynamical systems covering physical problems and mathematical modeling relevant to molecular biology, genetics, neurosciences, artificial intelligence as well as classic problems in mechanics, astronomy, and physics Demonstrates mathematic modeling relevant to molecular biology, genetics, neurosciences, artificial intelligence as well as classic problems in mechanics, astronomy, and physics.
From the Contents: Introduction -- Mathematical Neuroscience: from neurons to networks -- Jupiters belts, our Ozone holes, and Degenerate tori -- Analytical solutions of periodic motions in time-delay systems -- DNA elasticity and its biological implications -- Epidemiology, dynamics, control and multi-patch mobility.
Keywords: Dynamics; Nonlinear theories; Neural networks (Computer science) .; Nonlinear Optics; Bioinformatics; Graph theory; Applied Dynamical Systems; Mathematical Models of Cognitive Processes and Neural Networks; Nonlinear Optics; Computational and Systems Biology; Graph Theory